PERAN UNICEF (UNITED NATIONS CHILDREN’S FUND) DALAM MENANGANI ANAK-ANAK KORBAN KONFLIK DI PALESTINA - Ririn Suhasni Rahayu; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The protracted conflict between Israel and Palestine, resulted in a lot of damage, destruction and crisis of human rights. Therefore, many non-state actors have emerged to provide assistance to victims of the conflict in Palestine, especially for children. one of the international organizations that is active in providing assistance is UNICEF. Which in this case UNICEF helps realize children's rights by carrying out the role of UNICEF in dealing with children victims of the conflict in Palestine.The theoretical framework used in this study is the Pluralism Perspective using the International Organization theory, where UNICEF as an International Organization helps in providing children's human rights that they should get. The research method used in this study is a qualitative research method with research data collection techniques, namely primary data including official data from the UNICEF website and secondary data, namely data obtained from books, journals, media, and websites.The results of this study indicate that UNICEF has the responsibility to protect children and their basic rights which have been written in the convention on children's rights and the role of UNICEF both the initiator role, namely UNICEF in collaboration with various international communities such as collaborating with the Ministry of Health and WHO in the health sector. for children, infants and nursing mothers, UNICEF also collaborates with UNRWA in building schools and shelters and UNICEF collaborates with government and non-governmental organizations such as the education department, UNRWA, and local non-governmental organizations in implementing the program (PBEA). UNICEF also has a role as a Facilitator, one of which is investing in water treatment technology throughout the supply chain and UNICEF has a role as a Mediator, namely Monitoring Israel and Palestine to comply with the Convention on the right of the child (CRC). Keywords: UNICEF, Children Victims of Conflict, Palestine, Pluralism, International Organization Theory.